Effect of a physical training season applied on a U-19 male basketball team - Lopes, C. R.; da Mota, G. R.; Dechechi, C. J.; Tessutti, L. S.; Galatti, L. R. (International Journal of Sports Science, 2012)
This study aimed to analyze the effects of a specific physical training season, conducted concomitantly to the State championship, on muscle strength, speed and power in U-19 basketball players (n = 14; 18 ± 1 years old; 86.2 ± 10.2 kg of body weight; 1.92 ± 0.1 m of height). A double periodization model was used in the physical development program that was divided into the following periods: general preparatory, specific preparatory and competitive. The periodization was planned without any interference of the researchers. At five moments of the season (weeks 1, 8, 25, 39 and 49) the following parameters were assessed: maximal strength (1RM), sprints over 30 m (number of[NS]; mean speed over 30 meters (V30). maximal speed[Vmax]; time to attain maximal speed[AT]) and jumps (Squat Jump[SJ], counter-movement jump without arms[CMJ] and counter-movement jump with[CMJA]). The results showed that at the finals of the championship significant increases (p30 and AT were observed. The other parameters (1RM, SJ, CMJ, CMJA,Vmax and NS) did not change throughout the season (p>0,05). Thus, it can be concluded that only the time to attain it (acceleration) and V30 were sensitive to the training periodization proposed by the technical commission during the 49-week competitive season.